THE EFFECT OF USING CIRC TECHNIQUE ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMK TARUNA SATRIA PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Cindy Hanifa Marsya; Supriusman Supriusman; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Cooperative Integrated Reading and Composition (CIRC) technique is one of the techniques used to teach reading and writing, however the researcher only focus on reading comprehension. The research aimed at finding out whether there is a significant effect of using CIRC technique on the ability of the first year students in comprehending descriptive texts. 37 students of SMK Taruna Satria Pekanbaru were chosen as the sample of the research using cluster random sampling. The results of the research showed that there is a significant effect of CIRC technique on the ability of the first year students of SMK Taruna Satria Pekanbaru in comprehending descriptive texts. Based on the result, teacher can use CIRC technique to reading because this technique has proven to increase students’ reading comprehension of descriptive texts. Based on the results of the researcher, students are resumen to increase their ability level not only by doing exercise given by their teacher but also by doing them from the books.Key Words: Reading Comprehension, CIRC Technique, Descriptive Texts.